Migration and tax yields in a devolved economy - James S. Foreman-Peck; Peng Zhou (Cardiff University, Cardiff Business School, 2016)
Households may migrate between jurisdictions to secure preferred mixes of collectively sup-plied services and taxation. But devolution of taxes to sub-national jurisdictions could reduce expected tax revenue if some move to lower tax regimes, constraining devolved government policy. This paper develops an indirect approach to establish lower bound tax revenue impacts of possible tax changes by devolved governments. We estimate and aggregate migration responses to existing tax differentials between smaller, component administrative areas of the devolved jurisdictions. Because such existing taxes may have different bases from proposed devolved taxes, appropriate corrections are made in a model of the devolved economy. This model also establishes how the tax base and therefore the tax yield of the devolved economy, as well as the output per capita, would be changed by implementing different tax rates, given the migration responses estimated. The model is used to assess the fiscal possibilities for Wales created by the UK Government of Wales Act 2014.
Keywords: R23; J61; H11; H22; H71; H72; H77; 330; Migration; Fiscal Decentralisation; Tax Revenue